A Mild, One‐Pot Stadler–Ziegler Synthesis of Arylsulfides Facilitated by Photoredox Catalysis in Batch and Continuous‐Flow1. Issue 30 (19th June 2013) - Wang, Xiao; Cuny, Gregory D.; Noël, Timothy
<x xml:space="preserve">Abstract</x> Visible advance: A mild, one‐pot Stadler–Ziegler process for CS bond formation has been developed. The method employs the photoredox catalyst [Ru(bpy)3Cl2]⋅6 H2O irradiated with visible light. A variety of aryl–alkyl and diaryl sulfides were prepared from readily available arylamines and aryl/alkylthiols in good yields. The use of a photo microreactor led to a significant improvement with respect to safety and efficiency.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>